2015
DOI: 10.2135/cropsci2014.09.0599
|View full text |Cite
|
Sign up to set email alerts
|

Straw Incorporation Strategy on Cereal Crop Yield in China

Abstract: Straw incorporation (SI) is considered a valid agricultural measure for ameliorating soil quality and sequestrating soil C. This study aimed to quantitatively summarize the response of cereal yield to SI management. Our results showed that compared with straw removal, SI could significantly enhance cereal yield by 7% over all of China across the 9‐yr period. In all regions, SI in coarse‐textured soils increased yields more than in fine‐textured soils. Straw incorporation resulted in greater yield increases for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 37 publications
4
22
2
Order By: Relevance
“…3d) but increased thereafter. However, unlike several other studies Zhao et al, 2015), we observed that the yield increase tended to decline after a 15-year timespan of the adoption of straw incorporation (Fig. 3d).…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…3d) but increased thereafter. However, unlike several other studies Zhao et al, 2015), we observed that the yield increase tended to decline after a 15-year timespan of the adoption of straw incorporation (Fig. 3d).…”
contrasting
confidence: 99%
“…This yield increase is similar in magnitude to a recent global analysis (12%; Liu et al 2014), but larger 20 than previous meta-analyses of published data from China (up to 9% increase;Zhao et al, 2015;Wang et al, 2015;Huang et al, 2013;Xu et al, 2017) and those of the EU (6% increase; Lehtinen et al, 2014).…”
Section: Straw Incorporation Increased Crop Yieldsupporting
confidence: 87%
See 3 more Smart Citations